1971
DOI: 10.1271/bbb1961.35.1241
|View full text |Cite
|
Sign up to set email alerts
|

Production of L-Glutamic Acid from Hydrocarbon by Penicillinresistant Mutants of Corynebacterium hydrocarboclastus

Abstract: Penicillin-resistant mutants were derived from Corynebacterium hydrocarboclastus R-7. One of them produced 84g/liter of L-glutamic acid from hydrocarbon, though its parent strain •õ This paper was presented at the 19th Symposium on Amino Acid and Nucleic Acid held on 1st Decem ber,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The phospholipid composition as determined here is more or less in agreement with data published for C. glutamicum (15) and B. ammoniagenes (48). It differs significantly, however, from other coryneform glutamic acid-producing organisms which show extensive variations in the major components and in the occurrence of nitrogen-containing phospholipids (20,26,37).…”
Section: Hoischen and Kramer Materials And Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The phospholipid composition as determined here is more or less in agreement with data published for C. glutamicum (15) and B. ammoniagenes (48). It differs significantly, however, from other coryneform glutamic acid-producing organisms which show extensive variations in the major components and in the occurrence of nitrogen-containing phospholipids (20,26,37).…”
Section: Hoischen and Kramer Materials And Methodsmentioning
confidence: 81%
“…Several authors suggested that glutamate secretion may be induced by the presence of a specific phospholipid component (20,45). Both PIM and the amount of PA and DPG have been made responsible for regulating amino acid efflux (26,37). Thus, we analyzed the time course of the relative amount of every single phospholipid immediately after addition of biotin to biotin-limited producer cells.…”
Section: Hoischen and Kramer Materials And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison of Rf values of the phospholipids of E. coli, spots 1, 2, and 3 of N. erythropolis were considered to be PE, CL, and PG, respectively. TAKINAMI et al (12) and Ko-BAYASHI et al (13) reported that Corynebacterium hydrocarboclastus, which was reidentified later as N. erythropolis by KOMURA et al (14), contained PE, CL, phosphatidylinositol (PI), and phosphatidylinositolmannosides (PIM), and that the amount of PI was smaller than that of PIM. As shown in Fig.…”
Section: Identification Of Phospholipidsmentioning
confidence: 99%